Assessment of traditional healers' knowledge and utilization of pharmaceutical equipment and medical supplies in the Amhara region, North West Ethiopia - Liknaw Workie Limenh; Asmamaw Emagn Kasahun; Tewodros Ayalew Tessema; Yeniewa Kerie Anagaw; Wudneh Simegn; Wondim Ayenew (Taylor & Francis Group, 2024)
AbstractContext Although pharmaceutical equipment and medical supplies play a vital role in the quality of traditional medicines, they have not received much attention from stakeholders and researchers nationally and internationally.Objective This study assesses traditional healers' knowledge and utilization of pharmaceutical equipment and medical supplies in the Amhara region, North West Ethiopia.Materials and methods A quantitative cross-sectional study was conducted on 70 traditional healers. The data were collected using an interview-based questionnaire. The collected data were checked and entered into Statistical Package for Social Sciences version 25.0 for analysis. The results were presented as percentages. The association between socio-demographic characteristics and traditional healers' knowledge of pharmaceutical equipment and medical supplies was examined using Pearson's Chi-squares test.Results About 90% of traditional healers had information about pharmaceutical equipment and medical supplies, and currently 80% of them used different pharmaceutical equipment and medical supplies individually and in combination with traditional equipment. Although most traditional healers used different pharmaceutical equipment and medical supplies, only 13.3% of them used equipment and supplies a day. Only 15% of traditional healers continuously cleaned their equipment. None of the socio-demographic variables were significantly associated to the knowledge of pharmaceutical equipment and medical supplies.Discussion and Conclusions Pharmaceutical equipment and medical supplies used by traditional healers was inconsistent, mainly associated with their habit of using self-prepared and home-available equipment. Moreover, the checkup status of compounding equipment was poor. As Traditional healers provide high-patient care services, emphasis should be given to improving their preparation and treatment strategies.